A mixed methods exploration of family members'/friends' roles in a self-care intervention for depressive symptoms. (June 2014) - Sussman, Tamara; Yaffe, Mark; Mccusker, Jane; Burns, Victoria; Strumpf, Erin; Sewitch, Maida; Belzile, Eric
Objectives: The aims of this exploratory study were to examine the: (1) family and friend (F/F) support patients reported receiving and F/F reported providing to patients while participating in a self-care intervention (SCI) for depressive symptoms and (2) associations between different types of F/F support and patients' use of the self-care tools in the SCI. Methods: Fifty-seven patients aged 40 + participating in an uncontrolled feasibility study of an SCI, completed structured telephone interviews about the support they received from F/F while participating in the SCI. Eighteen F/F completed questionnaires on the support they provided to patients during the SCI. Seven F/F participated in a post-study qualitative interview on their involvement in the SCI. Results: About 35% of patients reported receiving F/F support with the SCI. Patients' use of the behavioral tools was positively associated with patients' report of F/F support, and with F/F's report of instrumental support provided. F/F reported uncertainty about the type of support they should offer to patients in the SCI. Discussion: F/F involvement in SCIs for depressive symptoms may be helpful to patients and may foster adherence to these interventions. More research is warranted on the nature of such involvement from the perspective of patients and F/F.